REPRESENTASI BUDAYA DALAM IKLAN: (Analisa Semiotika Iklan Marjan Versi Tari Betawi dan Sepatu Roda) - Dian Handayani (Jurnal Budaya Nusantara, 2019)
The purpose of this research is to understand the culture representation and the meaning ofBetawi dance and roller skate's version of Marjan advertising. This research used some theories,they are:Mass Communication, Advertising, Cultural Imagery, Semiotics, Culture Study, Semiologyby Roland Barthes. This research was analysed by Roland Barthles as denotation and connotationmeaning. This research showed that Marjan advertisement represented two cultures, they aretraditional culture through mask dance and modern culture trough roller skate's show. Thisadvertisement was successful to represent Betawi and modern culture through the show ofOndel-ondel who played the roller skates.